(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study reveals that the physio-chemical quality of water in wetlands, particularly in Hanumangarh, affects the number of migratory birds. The study found that annual temperature changes, which are closely linked to pH changes, lead to a decrease in migratory birds. The highest pH was found in Manaktheri pond, while the lowest was in Dablikhurd pond. Total dissolved solids (TDS) levels also impacted migrating birds, with Manakthri pond having the highest TDS and Dablikhurd pond have the lowest. Increased pollution led to a decrease in phytoplankton, the primary food source for migratory birds. The salinity of water also affected migrating birds. Factors contributing to the decline include environmental modifications, litter, water pollution, deforestation, trash removal, hazardous chemicals, human disturbance, pesticide spread, agrochemical contamination, global warming etc